Implementing Task-Based Language Teaching (TBLT) Instruction for Non-English Students - Khotimah, Khusnul; Asifin, Mochammad (English Language in Focus (ELIF), 2022)
Most of STMIK Yadika Bangil students are workers in some institution and foreign companies in Pasuruan District. The students are aware how important speaking skill either in study or in work life. However, previous background and students focus is not in studying English. Thus, it causes they seem to be shy exploring their idea, less-confident and be passive in speaking because they recognize that is difficult skill. This research is Class Action Research (CAR). The researcher concerns on their speaking participation rather than other skills because speaking is productive skill which can be directly and empirically observed. This research use TBLT (Task-Based Language Teaching) method to solve Informatics students in English class. This method is valued as effective and interactive way to create class to be more interactive each other. As one of the aim of TBLT method is to motivate students to be more active in speaking without burdening with structure or grammatical matter. The research methods used are literary study, observation and problem identification, method design and material preparation, implementation, analysis, discussing and conclusion. The results show that most students are more enthusiastic and more participative in speaking English and able to express ideas without having to be burdened with English grammatical or structure.